2021
DOI: 10.30935/cedtech/10945
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Distance Learning in Higher Education during COVID-19 Global Crisis: UAE Educators’ Perspectives

Abstract: The COVID-19 Pandemic affected all sectors worldwide including education sector changing the students learning environment at a large scale. In the education sector, governments had to close schools and universities around the world and turn into online mode of delivery. The sudden transformation to online learning demands educators and institutions to develop more innovative teaching methods in supporting students during this growing crisis. It is pertinent that this is the era of large-scale online learning,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…Concerning student-instructor interaction, most of the students found it easy to communicate (62.7%), ask questions (64.4%), and engage with the instructor during online classes (56.4%) and that the instructor was available during office hours (76.9%). This was a favorable result, as in an exploratory study among educators in the UAE, only one in five educators believed that online classes can promote student engagement [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Concerning student-instructor interaction, most of the students found it easy to communicate (62.7%), ask questions (64.4%), and engage with the instructor during online classes (56.4%) and that the instructor was available during office hours (76.9%). This was a favorable result, as in an exploratory study among educators in the UAE, only one in five educators believed that online classes can promote student engagement [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, assessing students' levels of attention was impossible due to a lack of real "face-to-face" eye contact. During the COVID-19, the results showed that distance learning is a great alternative to face-to-face instruction and that different teaching methods promote student participation and engagement in unique ways (Al-Karaki et al, 2021 ). Even though the findings of this study revealed that typing skills, creative skills, thinking skills, and listening skills impacted undergraduates’ academic performance and also found technical issues as impediments, all students did not have equal access to resources.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic is the key challenge to expanding academic performance, and this pandemic raised conversations about taking online teaching to a new level. Instead of offering a few selected, often online courses, universities had to turn full virtual programmes (Al-Karaki et al, 2021 ). In recent years, distance education has expanded quickly at all levels around the world.…”
Section: Introductionmentioning
confidence: 99%
“…These media had been in existence for some time, but it became prominent because of the pandemic. Studies have posited on its effectiveness, the technical competence, teaching models, as well as the rationale, especially during Covid-19 (Al-karaki, et al, 2021;Caputo et al, 2021;Viegas et al, 2018). These studies have considered remote learning as a credible alternative to face-to-face learning with better options in autonomy of learning, flexible pedagogy (synchronous and asynchronous) and virtual laboratory in instances of absent physical laboratory equipment in teaching STEM courses.…”
Section: Literature Reviewmentioning
confidence: 99%